Comparison between the free deep inferior epigastric perforator (diep) flap and muscle sparing (ms) free transverse rectus abdominis myocutaneous (tram) flap for breast reconstruction - Ahmed Ragab Morsi; Ahmed Adel Nour Eldin; Ahmed Fathy Aborady; Ashraf Abolfotouh Khalil (Cairo : Ahmed Ragab Morsi, 2014)
Since it was first described in 1979, the free transverse rectus abdominis myocutaneous (TRAM) flap has become one of the most popular and reliable methods of microsurgical breast reconstruction in breast cancer patients. Over time, the free TRAM flap has evolved to include the muscle-sparing (MS) TRAM flap and the deep inferior epigastric perforator (DIEP) flap, to minimize donor site morbidity. Both the free MS-TRAM and DIEP flap methods involve transferring skin and subcutaneous tissue from the lower abdominal area to obtain an aesthetically pleasing breast reconstruction . DIEP and MS-TRAM flaps offer the patient the same advantages as the pedicled TRAM-flap and discarded the most important disadvantages. The donor site morbidity, ill-defined infra-mammary crease, post-operative pain and time for recovery
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of General Surgery
Issued also as CD
Keywords: DIEP; MS; TRAM